2022
DOI: 10.3233/shti210871
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-Based Self-Care Application for COVID-19: Development Process Using the ADDIE Model

Abstract: During the COVID-19 era, technology-enhanced protection of this disease has saved lives in developed countries in which citizens have the privilege of accessing and using such technologies to fight Coronavirus. In the undeveloped countries, on the other hand, citizens have had no accession or ability to use digital technologies to prevent COVID-19. Having this in front, in the MyShield research project, we aim to address how to teach self-care skills in undeveloped countries in the era of COVID-19 using a mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In fact, providing free services to patients is one of the motivating factors for patients to use technology, which was the concern of patients and specialist physicians in our study. However, some technology-based products are expensive, this issue can affect the number of users [ 26 ]. In addition, the high cost of designing and developing some technology-based products can also affect the technology distribution policies of healthcare providers [ 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, providing free services to patients is one of the motivating factors for patients to use technology, which was the concern of patients and specialist physicians in our study. However, some technology-based products are expensive, this issue can affect the number of users [ 26 ]. In addition, the high cost of designing and developing some technology-based products can also affect the technology distribution policies of healthcare providers [ 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to design our app user interface to better communicate with patients, we sought out experts in user experience and software in these fields. This method of designing an app's user interface and user experience flow has been used in a number of studies [40,41]. It is important to note that a good user interface design is very important to a mobile app's acceptance by its users [42].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, in addition to con rming it, we found the simple and user-friendly design of technologies as a positive factor. It should be noted that the design of the appropriate user interface makes the users more persuasive and this issue makes it easier for the patient to accept the designed system (10,28,29).…”
Section: Discussionmentioning
confidence: 99%